How the human arrived in Islam and then disappeared - Touati, Houari. (Leiden ; Boston)
viii, 544 sayfa
Keywords: “This book argues that while the concept of the human being was a Greek invention, its reinvention was Arab before it was European. Born in Greece in the fourth century BCE, this concept of the human being disappeared at the end of Late Antiquity, before reappearing in the Abbasid Near East. It was Muslim rationalist theologians who revived it in their theodicy of a just God who can only be just by recognizing the agency of human beings in their voluntary acts. Later, Arabic-speaking philosophers gave it a space of its own under the name of 'human sciences,' in the 9th century. But a traditional theology got the better of it. Its reappearance had to wait for the European Renaissance, while retaining its Arab origins.“ --